Pengaruh Penggunaan Whatsapp Terhadap Kemampuan Bahasa Indonesia Yang Baik dan Benar (Studi Kasus Pada Mahasiswa Kelas 4g Fti Unmer Malang - Asrofi Asrofi; Avelina Apridiani (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
Indonesia is the 3rd country with the most WhatsApp users out of 11 countries in 2023 with a percentage of 92.1% users. With this large population of users, WhatsApp is one of the most influential social media and much loved by the people of Indonesia. Likewise, students in Indonesia in this digital era have used the WhatsApp application for their communication needs with campus friends, family and other acquaintances. This also applies to students in the 4G class of the Faculty of Information Technology, Merdeka University Malang. The purpose of writing this article is to find out and describe the proper and correct use of Indonesian in the communication process via WhatsApp application with the object of research being conducted by 4G class students of Fti UNMER Malang. The author uses a qualitative descriptive research method, data collection techniques carried out by distributing questionnaires through the Google form link which can be accessed by 4G class students of FTI UNMER Malang. The results of this study show that WhtasApp has a positive and negative influence on good and correct Indonesian language skills.